Peran Guru dalam Meningkatkan Kualitas Pembelajaran IPS di Sekolah Dasar Melalui Pendekatan Deep Learning - Dwitami, Dena; Khaerunisa, Ines; Fuadah, Intan Samrotul; Wati, Talitha Arista; Arifin, Muh. Husen (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Social studies learning in elementary schools plays a crucial role in shaping students' character, social insight, and critical thinking skills. However, its practice is still dominated by lecture methods and lacks contextualization. This study aims to describe the role of teachers in improving the quality of social studies learning through a deep learning approach. The method used is a literature review, analyzing literature related to the concept, implementation, and strategies of deep learning in elementary education. The results of the study indicate that deep learning encourages active student engagement through exploratory, collaborative, and reflective activities. Teachers act as designers, facilitators, and evaluators of learning that emphasizes the process and character development. This approach makes social studies learning more meaningful, contextual, and supports the mastery of 21st-century competencies